Zein Nanoparticles and Strategies to Improve Colloidal Stability: A Mini-Review - Pascoli, Mônica; de Lima, Renata; Fraceto, Leonardo F. (Frontiers in Chemistry, 2018)
Zein, a protein extracted from maize, can be employed to easily produce nanoscale particles suitable for use as carrier systems. This review investigates the main methods for obtaining zein nanoparticles, as well as the problems and options available in the development of stable colloidal suspensions. Considerable gaps were identified in the literature concerning this topic, with studies being unclear about the factors that affect the stability of zein particles. In the vast majority of cases, no data are presented in relation to the stability of the formulations over time. It could be concluded that in order to produce a high quality system, detailed evaluation is required, considering factors including the zein concentration, pH, ionic strength, thermal treatment of the protein prior to preparation of the nanoparticles, strategies employing other materials as coatings, and the storage conditions. It is extremely important that these aspects should be considered during product development, prior to commercial-scale manufacture.